Performance Management and Appraisal in Human Service Organizations: Management and Staff Perspectives - Selden, Sally; Sowa, Jessica E. (Public personnel management, 2011)
To demonstrate their effectiveness, nonprofit organizations, like public and private sector organizations, are facing increasing pressure to demonstrate how well they perform and their plans for future improvement. An essential part of this process of measuring and fostering effectiveness is managing the performance of organizational members; typically this is accomplished with performance management processes, as the ability of nonprofit organizations to meet their goals is directly dependent upon the ability of the staff to perform effectively in the management and delivery of services. Performance management systems have been studied extensively in the public and for-profit sectors but have not been adequately explored in the nonprofit sector to surface possible sector-specific challenges. This study addresses this gap in the nonprofit knowledge base by comparing the utilization of different components of a performance management system from the perspective of management and frontline staff. It identifies gaps in the perceptions of management and staff concerning performance management and identifies five different models of performance management systems, concluding with lessons for practice.